Lunar Radiometric Measurement Based on Observing China Chang’E-3 Lander with VLBI—First Insight - SongTao Han; ZhongKai Zhang; Jing Sun; JianFeng Cao; Lue Chen; Weitao Lu; WenXiao Li (Advances in Astronomy)
China Chang’E-3 performed soft landing at the plains of Sinus Iridum on lunar surface on December 14th 2013 successfully; it opened a new window for observing lunar surface with radiometric tracking which many lunar scientific researchers always pursue for. Since July 2014, OCEL (Observing Chang’E-3 Lander with VLBI) project has been conducted jointly by IVS (International VLBI Service of Geodesy and Astrometry) and BACC (Beijing Aerospace Control Center), a global IVS R&D network augmented with two China Deep Space Stations configured for OCEL. This paper presents the current status and preliminary result of the OCEL and mainly focuses on determination of the lander position, which is about 7 meter in height and 14 meter in plane of lunar surface with respect to LRO (Lunar Reconnaissance Orbiter). Based on accuracy analysis, further optimized OCEL sessions will make use of this target-of-opportunity, the Chang’E-3 lunar lander, as long as it is working. With higher accurate radiometric observables, more prospective contribution to earth and lunar science is expected by combining with LLR.